Production capacity losses analysis in manufacturing sector : A case study of UAE ductile iron pipes manufacturing industry - Bamatraf, Fahmi Jamil Umer (2018)
Production capacity is referred as the total throughput a company, machine or system can produce. Several production systems are around us in various sectors. In manufacturing sector, there are possibilities of production losses due to various factors. Downtime cases, machine or human errors, faulty equipment or traditional production system all are source of production capacity losses in manufacturing sector. The aim of this project is to conduct analytic study of production capacity losses in manufacturing industries. The project takes ductile iron pipes industry in United Arab Emirates (UAE) as a case study of the production capacity losses investigation. The research data were collected in two ways, the first one by getting the data from selected company in UAE by visiting the company and observing the process and recording the required data. The second way of data collection was through questionnaire distribution to the consumers who utilize the company products. The collected data were analyzed and investigated along with suggestion of the most appropriate capacity planning approaches. The proposed approaches aimed to reduce the company production losses and increase their throughputs to meet customers’ requirements. Hence the objectives of this project were successfully achieved through analysis and investigation of production capacity losses in ductile iron Pipes Company in UAE. The proposed approaches in this project are effective and can be implemented in other industries to reduce their production capacity losses and enhance their production cycle.